Identification of fuel oil in non-absorbent surfaces in a site of ANFO blasts - Phang, Cheah Chaw (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
ANFO, a commercial explosive consists of mixture of fuel and oxidizer, none of which is classified as explosive. ANFO is usually used in construction, quarrying and mining works but sometimes it is identified as one of the most common explosion found in a crime scene. They are often mixed at different ratio by a non-standard user during explosion. Therefore, the objective of this project is to serve as a preliminary study to investigate how far ANFO at different mixing ratio can travel after the blasts. Five different mixing proportions of AN and FO (94:6, 90:10, 80:20,60:40 and 50:50) were used in this studies. Six selected non-absorbent surfaces commonly found at an explosion scene were placed at the distance of 5 m, 7 m and 9 m radius from the seat of blast. Residues travelled on selected surfaces were collected and analyzed using GC-MS. As a result, the FO residues can travel as far as 7 meter with the idea ANFO mixture of94:6 by weight (500 g AN and 38.35 mL FO) during blasting. When improper ANFO mixture of 50:50 by weight (500 g AN and 600.96 mL FO) was used, explosion did occur but FO found splashed and scattered around the crater mark. Thus, the extent of FO residues travel to some distances after the blast depends upon the proportions and quantities of ANFO.